A Critical Review of Shonitasthapana Varga Dravyas on Rakta Dhatu - Naveen V; MS Veena Mullur (RGUHS Journal of AYUSH Sciences)
Classification of dravyas based on karma and scientific rationality of assigning them into particular vargas or groups is one of the hallmarks of our Acharyas in Ayurveda. Shonitasthapana varga dravyas mentioned by Charaka and Vagbhata is a distinctive group for the diversity of its sources as well as actions. A critical analysis of Shonitasthapana varga dravyas based on literature review of classical texts commentators research works etc. revealed varied actions of the dravyas which can be categorized into raktavardhana raktaprasadana and raktasthambana karmas. The group includes sthavara five drugs jangama one drug oudbida two drugs and ahara dravyas two dravyas which add to the uniqueness of being used as oushada as well as pathya. The judicious use of these dravyas after ascertaining their qualities and pharmacological activities offer a wide scope for utility of these drugs in various hematological disorders.